2015
DOI: 10.1016/j.canlet.2015.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule inhibitor of the bone morphogenetic protein pathway DMH1 reduces ovarian cancer cell growth

Abstract: The bone morphogenetic protein (BMP) pathway belonging to the Transforming Growth Factor beta (TGFβ) family of secreted cytokines/growth factors is an important regulator of cancer. BMP ligands have been shown to play both tumor suppressive and promoting roles in human cancers. We have found that BMP ligands are amplified in human ovarian cancers and that BMP receptor expression correlates with poor progression-free-survival (PFS). Furthermore, active BMP signaling has been observed in human ovarian cancer tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 72 publications
(89 reference statements)
1
27
0
Order By: Relevance
“…We also used a small-molecule inhibitor of BMP signaling, DMH1, to block pathway activity. DMH1 can suppress the growth of BMP-dependent ovarian and lung cancer cells (36,37), but its efficacy in melanoma has not been reported. DMH1 inhibits the kinase activity of ALK2 and BMPR1A (ALK3) receptors but not of BMPR1B (ALK6), thereby abrogating phosphorylation and activation of the SMAD1/5/8 transcriptional cascade (38).…”
Section: Resultsmentioning
confidence: 99%
“…We also used a small-molecule inhibitor of BMP signaling, DMH1, to block pathway activity. DMH1 can suppress the growth of BMP-dependent ovarian and lung cancer cells (36,37), but its efficacy in melanoma has not been reported. DMH1 inhibits the kinase activity of ALK2 and BMPR1A (ALK3) receptors but not of BMPR1B (ALK6), thereby abrogating phosphorylation and activation of the SMAD1/5/8 transcriptional cascade (38).…”
Section: Resultsmentioning
confidence: 99%
“…We used a CRISPR (clustered regularly interspaced short palindromic repeat)-screen dataset from ten cell lines of various tissue types to identify HGSC-specific essential genes (Hart et al, 2015). Inspection of genes with a high frequency of essentiality, as well as high expression in HGSC cell lines and tumors, confirmed known proto-oncogenic targets in ovarian cancer, including ERBB3, EPHB4, and BMPR1A, which contribute to cell survival and chemotherapeutic resistance (Hover et al, 2015;Kumar et al, 2007;Sheng et al, 2010). Our integrated (C-E) Expression and essentiality of (C) receptor tyrosine kinases (RTKs) and serine/threonine kinases (STKs), (D) tetraspanins and integrins, and (E) G-proteincoupled receptors (GPCRs) in HGSC cell lines and TCGA tumors.…”
Section: Functional Surfaceome Of Hgscmentioning
confidence: 99%
“…These newer molecules specifically target BMP signaling but not VEGF and angiogenesis 19 . DMH1 has been shown to promote cardiac differentiation in mouse embryonic stem cells 38 and facilitate neurogenesis of human-induced pluripotent stem cells 39 , and inhibit ovarian cancer cell growth 40 . In this study, we found that DMH1 significantly inhibited Pi and BMP2-induced calcium deposition in HASMCs as revealed by Alizarin Red S staining and calcium assay.…”
Section: Discussionmentioning
confidence: 99%